Framing and visual type: Effect on future Zika vaccine uptake intent - Jeanine P.D. Guidry; Kellie E. Carlyle; Jessica G. LaRose; Paul Perrin; Mark Ryan; Marcus Messner; Jay Adams (SAGE Publishing, 2018)
Introduction: The Zika virus is associated with the birth defect microcephaly, and while a vaccine was not available in early- 2017, several were under development. This study's purpose was to identify effective communication strategies to promote uptake of a new vaccine, particularly among women of reproductive age. Design and methods: In order to study the effects of Zika message framing (gain vs. loss) and visual type (photo vs. infographic) on future Zika vaccine uptake intent, a 2×2 between-subjects experiment was performed via an online survey in 2017 among 339 U.S. women of reproductive age (18-49 years). Participants were exposed to one of four messages, all resembling Instagram posts: gain-framed vs. loss-framed infographic, and gain-framed vs. loss-framed photo. These messages were followed by questions about Zika vaccine uptake intent as well as intermediate psychosocial variables that could lead to intent. Results: There was no interaction between framing and visual type (P=0.116), and there was no effect for framing (P=0.185) or visual type (P=0.724) on future Zika vaccine uptake intent, which is likely indicative of insufficient dosage of the intervention. However, when focusing on intermediate psychosocial constructs that are known to influence behavior and intent, gain-framed messages were more effective in increasing subjective norms (P=0.005) as related to a future Zika vaccine, as well as perceived benefits (P=0.016) and self-efficacy (P=0.032). Conclusions: Gain-framed messages seem to be more effective than loss-framed messages to increase several constructs that could, in turn, affect future Zika vaccine uptake intent. This is a novel finding since, traditionally, loss-framed messages are considered more beneficial in promoting vaccine-related health behaviors.